Willingness to Communicate in L2 English Remote Language Learning: Dual Qualification Students’ Perceptions - Lyytikäinen, Riikka (My University, 2022)
This thesis investigated willingness to communicate (WTC) among dual qualification students learning English as a second language (ESL) during the COVID-19 pandemic. The aim of the present study was to discover how willing the learners were to communicate in remote English lessons, also in comparison with traditional classroom learning. Other key goals of the research were to investigate the perspectives of the learners on how their WTC in remote learning settings could be increased, and to examine how their WTC had changed over time during the pandemic. The research data were collected via self-reported online survey, and it reached 47 dual qualification students in Proper Finland area. The study was conducted as a mixed-methods research, so both quantitative and qualitative data were gathered and analyzed. According to the study results, the participants’ average WTC scores for all the listed lesson activities were lower in remote learning settings compared to traditional classroom lessons. The result was statistically significant. The participants’ general WTC in remote lessons was from low to moderate. The results suggested that the participants’ views on how to increase their English WTC in remote lessons included, for example, working in small groups, others students’ participation and activeness during remote lessons or, in other words, the action of other students in the group, and non-voluntariness in responding. Approximately a third of the participants considered their WTC having at least somewhat changed during the years of the pandemic. There were both shifts to increased WTC and decreased WTC. Further studies need to be conducted in WTC in remote learning settings to gain a deeper knowledge on WTC in modern online learning environments. More research ought to be conducted in larger study samples, utilizing mixed-methods research, for example.
Keywords: English as a foreign language, remote learning, second language acquisition, willingness to communicate.